Guest editors' note - Van Dyk, Tobie; Rambiritch, Avasha (Journal for Language Teaching, 2022)
Adelia Carstens retired as full professor and director of the Unit for Academic Literacy, University of Pretoria, after an academic career spanning nearly 40 years, but continues to remain a valued colleague and expert in the fields that she has worked in. In the course of her academic career, she has taught close to 23 different modules from first year to master’s level, successfully supervised several postgraduate students, designed and developed highly successful writing and communication modules, and contributed greatly to the advancement of the University of Pretoria through her work in the development of this institution’s language policy, its language planning and overall language support from undergraduate to postgraduate level. She has mastered and published extensively on academic writing at undergraduate and postgraduate level, course and syllabus design, academic reading, genre-focused teaching of writing, translanguaging and multilingualism, to name a few. Adelia holds two PhDs, one from UNISA and one from the University of Pretoria. She has also been involved in large scale national projects, as well as international collaborative efforts. She holds a C2 NRF rating.